Novel imaging biomarkers for mapping the impact of mild mitochondrial uncoupling in the outer retina in vivo. - Bruce A Berkowitz; Hailey K Olds; Collin Richards; Joydip Joy; Tilman Rosales; Robert H Podolsky; Karen Lins Childers; W Brad Hubbard; Patrick G Sullivan; Shasha Gao; Yichao Li; Haohua Qian; et al. (PLoS ONE)
Purpose To test the hypothesis that imaging biomarkers are useful for evaluating in vivo rod photoreceptor cell responses to a mitochondrial protonophore. Methods Intraperitoneal injections of either the mitochondrial uncoupler 2,4 dinitrophenol (DNP) or saline were given to mice with either higher [129S6/eVTac (S6)] or lower [C57BL/6J (B6)] mitochondrial reserve capacities and were studied in dark or light. We measured: (i) the external limiting membrane-retinal pigment epithelium region thickness (ELM-RPE; OCT), which decreases substantially with upregulation of a pH-sensitive water removal co-transporter on the apical portion of the RPE, and (ii) the outer retina R1 (= 1/(spin lattice relaxation time (T1), an MRI parameter proportional to oxygen / free radical content. Results In darkness, baseline rod energy production and consumption are relatively high compared to that in light, and additional metabolic stimulation with DNP provoked thinning of the ELM-RPE region compared to saline injection in S6 mice; ELM-RPE thickness was unresponsive to DNP in B6 mice. Also, dark-adapted S6 mice given DNP showed a decrease in outer retina R1 values compared to saline injection in the inferior retina. In dark-adapted B6 mice, transretinal R1 values were unresponsive to DNP in superior and inferior regions. In light, with its relatively lower basal rod energy production and consumption, DNP caused ELM-RPE thinning in both S6 and B6 mice. Conclusions The present results raise the possibility of non-invasively evaluating the mouse rod mitochondrial energy ecosystem using new DNP-assisted OCT and MRI in vivo assays.